Applicability of a multiplex PCR to detect O26, O45, O103, O111, O121, O145, and O157 serogroups of Escherichia coli in cattle feces - Paddock, Zachary Dean; Shi, Xiaorong; Bai, Jianfa; Nagaraja, Tiruvoor G. (My University, 2012)
Shiga toxin-producing Escherichia coli (STEC), particularly O157, are major food borne pathogens. Non-O157 STEC, particularly O26, O45, O103, O111, O121, and O145, have also been recognized as a major public health concern. Unlike O157, detection procedures for non-O157 have not been fully developed. Our objective was to develop a multiplex PCR to distinguish O157 and the ‘top six’ non-O157 serogroups (O26, O45, O103, O111, O121, and O145) and evaluate the applicability of the multiplex PCR to detect the seven serogroups of E. coli in cattle feces. Published sequences of O-specific antigen coding genes, rfbE (O157) and wzx and wbqE-F (non-O157), were analyzed to design serogroup-specific primers. The specificity of amplifications was confirmed with 138 known STEC strains and the reaction yielded the expected amplicons for each serogroup. In feces spiked with pooled 7 STEC strains, the sensitivity of the detection was 4.1 X 10[superscript]5 CFU/g before enrichment and 2.3 X 10[superscript]2 after 6 h enrichment in E. coli broth. Additionally, 216 fecal samples from cattle were collected and tested by multiplex PCR and cultural methods. The multiplex PCR revealed a high prevalence of all seven serogroups (178 [O26], 108 [O45], 149 [O103], 30 [O111], 103 [O121], 5 [O145], and 160 [O157]) of 216 samples in fecal samples. Cultural procedures identified 33.1% (53/160) and 35.5% (11/31) of PCR-positive samples for E. coli O157 and non-O157 serogroups, respectively. Samples that were culture-positive were all positive by the multiplex PCR. The multiplex PCR can be used to identify serogroups of putative STEC isolates.
Keywords: Shiga toxin-producing E. coli; Multiplex PCR; Cattle; Feces